A promising role of cinnamon towards rheumatoid arthritis - Almulathanon, Ammar A. Y; Sideek Tawffiq, Zena (Vojenské zdravotnické listy, 2023)
Rheumatoid arthritis (RA) is a chronic disorder manifested by joint damage due to inflammation and autoimmunity which in turn has significant impacts on a patient's lifestyle. During disease, inflammation occurs due to activation of different immune cells, including macrophages and lymphocytes. Currently, the mainstay of treatment for RA is drug therapy. However, drug options are limited due to their negative effects and the possibility of reducing therapeutic benefits over time. Therefore, an effective and tolerable alternative therapy is needed. Several natural products have been found to have anti-inflammatory and anti-oxidant effects by affecting multiple molecular targets such as transcription factors and cytokines. Cinnamon, an aromatic plant, is a popular spice used for cooking and in traditional medicine all over the world. Cinnamon is composed mostly of essential oils and various components, such as cinnamaldehyde and eugenol. This review demonstrates the anti-inflammatory activity of cinnamon components in various preclinical and clinical studies illustrating their potential role in the treatment of RA.
Keywords: Aldehydes; antiflogistika; cytokiny; Inflammation; léčivé rostliny; Cinnamomum; zánět; aldehydy; Plants, Medicinal; Arthritis, Rheumatoid; Cytokines; revmatoidní artritida; skořicovník; Anti-Inflammatory Agents